Analisis Pengaruh Pendidikan, Pertumbuhan Penduduk dan Investasi terhadap Kemiskinan di Kalimantan Selatan - Safitri, Leli; Effendi, Muhammad (PPJP ULM, 2019)
Poverty is a complex problem in a development and related to many aspects.The problem of poverty has a close relation with low level of income received by thelabors which caused of education quality that still in low level, the population growthwhich relatively high may caused more unemployment, a different growth ofinvestment in every region that may difficult to create more job field for poor people,if economic growth in a region only dominated by a certain production activities andusing more labors with high education background from other regions, and it causedpoor people should to live in poverty circle.This research is a quantitative research and using the analysis of paneldata.Data from period 2013-2017 and which including all of the regencies/cities inSouth Kalimantan that consists of 13 regencies/cities. The purpose of this research isto analyze how big the effect of education, population growth and investment towardspoverty in South Kalimantan.The result shows that education has a negative effectand not significant, population growth has a negative effect and significant andinvestment has a positive effect and not significant towards poverty in SouthKalimantan.